Political participation of street vendors and Government officials (Study in Pontianak City Indonesia) - Elyta,; Herlan,; Burhanduddin, (Technium Social Sciences Journal, 2020)
This study focused on the political participation of street vendors and government officials. The government officials are a person who has been appointed by officials who have the power with the aim of so can do some business or activity, which is the duty and obligation of the government to achieve the state's goals. Government officials include the mayor, legislators, Subdistrict Head, Small-Subdistrict Head, Head of hamlet, neighbourhood, and some existing enforcement officials' administrative fields. Research methods in this observation type of research are descriptive qualitative, which is a kind of observation in the presentation of descriptive data in the form of a sentence structure that can be studied. The study was qualitative form an inductive approach in the design of sciencebased research and focused on the understanding of the experience. In this observation that an informant is the ethnic Malay community. How to get information using purposive sampling techniques, which means making the subject of research that has been included in the category. As for the informant is ten hawkers. The method used is shaped informant interviews with technical guidelines to help conduct interviews that comply with the standards with questions directly—using structured interviews to obtain information regarding viewpoints, insights, and experiences that provide in the form of oral or greeting openly. The escort process of data collection is done by selecting informants by the categories of samples as well as confidence in the informer. During the interview process, researchers used a tape recorder and a small note which serves to describe the current conditions when conducting interviews. The research found the close relationship between the level of income with connections made hawkers and political officials. Matters relating to the administrative officer who became the talk of the form of business organization means that issues relating to the license, places, and anything that can be used as a business.